2021
DOI: 10.4085/1062-6050-0618.20
|View full text |Cite
|
Sign up to set email alerts
|

Positive Reframing: An Important but Underutilized Coping Strategy in Athletes Undergoing Sport-Related Knee Surgery

Abstract: Context: It is unknown how specific coping strategies are associated with the short-term outcomes among athletes following knee surgery. Objective: 1) To determine whether specific coping strategies are associated with satisfaction, return to sport, self-reported knee function, or kinesiophobia following sports-related knee surgery. 2) To determine whether these associations vary by age, sex, or surgical procedure. Study design: Case series. Methods: Athletes (n=184… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…It has been suggested that cognitive behavioral therapies and resilience training can improve coping strategies and decrease psychological distress in patients undergoing knee surgery. 47 This, in turn, may have positive effects on other psychological factors (e.g., fear avoidance), physical activity adherence, and HRQOL (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that cognitive behavioral therapies and resilience training can improve coping strategies and decrease psychological distress in patients undergoing knee surgery. 47 This, in turn, may have positive effects on other psychological factors (e.g., fear avoidance), physical activity adherence, and HRQOL (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…Stress, defined as the body's response to any demand or threat, however, can pose a significant threat to one's emotional stability and overall mental well-being (Schneiderman et al, 2005). Nevertheless, not all stress is "bad" or inherently negative (Selye, 1973); depending on the circumstances, stressful or challenging experiences can foster personal and professional growth (Flanigan et al, 2021;Hughes et al, 2011;Robbins et al, 2019;Selye, 1973).…”
mentioning
confidence: 99%